Pendampingan Kewirausahaan dalam Peningkatan Kinerja Pelaku UMKM Di Desa Purwobinangun - Rialdy, Novien; Melisa, Ahdwi Tia (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service activity aims to provide socialization regarding knowledge about entrepreneurship and knowledge about the economy in order to gain understanding and ultimately improve business. Increasing business so that it can increase profits and increase the GDP of the city of Depok. This community service activity went smoothly and was attended by participants as expected. The implementation of this assistance through outreach about entrepreneurial activities in Purwobinangun Village starts on 11 August - 26 August 2022. In addition, participants were able to understand material about entrepreneurship and the economy, as indicated by the question and answer and active participation of most of the participants. Based on the results of this community service implementation, the next community service participants can improve their abilities and entrepreneurial spirit in a more compact manner, namely for those whose businesses are similar or have similarities with the goal if there is a large order they can be done collectively